Optical sensor to support nitrogen fertilization recommendation for sugarcane crops - do Amaral, Lucas Rios; Molin, José Paulo (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the potential of a terrestrial active optical sensor to support nitrogen fertilization recommendation, in variable rates, for sugarcane crops. Experiments in a randomized complete block design were carried out with different N rates (0, 50, 100, 150 and 200 kg ha-1). The response of sugarcane to N was evaluated by different methods – optical sensor, chlorophyll meter, and leaf N content –, when the average height of stalks was 0.2, 0.4 and 0.6 m. A low correlation was observed between leaf N content and the amount of chlorophyll measured by a portable chlorophyll meter. Therefore, these two methods were insufficient to evaluate the efficiency of the optical sensor, since the measured values increased with the amount of N applied. The strategy of fertilization recommendation based on crop response, estimated by the optical sensor in a sugarcane strip that received the appropriate N rate, was more consistent with the obtained yield. The optical sensor is a useful tool to recommend N for sugarcane crops, taking into account the spatial variability of N demand.
Keywords: Saccharum; nitrogen; precision agriculture; remote sensing